PEMBERDAYAAN MASYARAKAT MELALUI WORKSHOP IDE BISNIS DAN MANAJEMEN KEUANGAN SEDERHANA - Daga, Rosnaini; Salam, Karta Negara; Mujahid, Mujahid; Verawaty, Verawaty; Pratiwi Ar, Dhita; Hamdat, Aminuddin; Rizal, Muhammad; Baharuddin, Ceskakusumadewi; Musdalifah, Musdalifah (Yayasan Education and Social Center, 2025)
This community service activity aims to increase the community's capacity and economic independence through training in identifying and formulating potential business ideas, along with a basic understanding of simple financial management. This activity is conducted as an interactive workshop involving participants from productive community groups in the target area. The implementation method includes socialization, training, mentoring, and evaluation of the activity's results. Through this activity, participants are guided to explore local potential for business opportunities and develop simple, realistic and sustainable business plans. In addition, participants receive training in business financial management, including recording income and expenses, budget planning, and the importance of separating personal and business finances. The results of the activity indicate an increase in participants' knowledge and skills in formulating business ideas and their ability to manage budgets more effectively. This activity is expected to foster an entrepreneurial spirit, increase community economic independence, and serve as the first step towards establishing micro-enterprises based on local potential.